Cisplatin Selects for Multidrug-Resistant CD133+ Cells in Lung Adenocarcinoma by Activating Notch Signaling - Liu, Yu-Peng; Yang, Chih-Jen; Huang, Ming-Shyan; Yeh, Chi-Tai; Wu, Alexander T.H.; Lee, Yu-Cheng; Lai, Tsung-Ching; Lee, Chien-Hsin; Hsiao, Ya-Wen; Lu, Jean; Shen, Chia-Ning; Lu, Pei-Jung; et al. (Cancer research (Chicago, Ill.), 2013)
Platinum-based chemotherapy is the first-line treatment for non–small cell lung cancer, but recurrence occurs in most patients. Recent evidence suggests that CD133+ cells are the cause of drug resistance and tumor recurrence. However, the correlation between chemotherapy and regulation of CD133+ cells has not been investigated methodically. In this study, we revealed that CD133+ lung cancer cells labeled by a human CD133 promoter–driven GFP reporter exhibited drug resistance and stem cell characteristics. Treatment of H460 and H661 cell lines with low-dose cisplatin (IC20) was sufficient to enrich CD133+ cells, to induce DNA damage responses, and to upregulate ABCG2 and ABCB1 expression, which therefore increased the cross-resistance to doxorubicin and paclitaxel. This cisplatin-induced enrichment of CD133+ cells was mediated through Notch signaling as judged by increased levels of cleaved Notch1 (NICD1). Pretreatment with the γ-secretase inhibitor, N-[N-(3,5-difluorophenacetyl)-1-alanyl]-S-phenylglycine t-butyl ester (DAPT), or Notch1 short hairpin RNAs (shRNA) remarkably reduced the cisplatin-induced enrichment of CD133+ cells and increased the sensitivity to doxorubicin and paclitaxel. Ectopic expression of NICD1 reversed the action of DAPT on drug sensitivity. Immunohistochemistry showed that CD133+ cells were significantly increased in the relapsed tumors in three of six patients with lung cancer who have received cisplatin treatment. A similar effect was observed in animal experiments as cisplatin treatment increased Notch1 cleavage and the ratio of CD133+ cells in engrafted tumors. Intratumoral injection of DAPT with cisplatin treatment significantly reduced CD133+ cell number. Together, our results showed that cisplatin induces the enrichment of CD133+ cells, leading to multidrug resistance by the activation of Notch signaling. Cancer Res; 73(1); 406–16. ©2012 AACR.